Edukasi Ternak Lele Dalam Ember dan Pemanfaatan Airnya Sebagai Pupuk Tanaman - Alfahnum, Mal; Masitha Astriani, Maya; Haryo Basuki, Kasih (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The problem of increasingly scarce land for fish farming and water for fisheries activities can be overcome with the help of technology. With the use of more creative small spaces and conservation of cultivation water. This community service activity aims to provide education and training to students of SMK Al Wahyu Ciracas, East Jakarta about catfish farming in buckets and the use of water as plant fertilizer to overcome the problems of business activities carried out on limited land. Community service activities were carried out on 50 students of SMK Al Wahyu Ciracas, East Jakarta. The implementation of community service was carried out by socializing and demonstrating budikdamber and utilizing its wastewater. This activity resulted in an increase in participants' knowledge and skills by 88% about budikdamber and the use of water as plant fertilizer. Catfish farming in buckets can be a solution to providing fish and vegetables simultaneously for limited land and more efficient water use, increasing family independence (nutritional needs and income), and is easy to do at home with relatively little capital. budikdamber produces wastewater that can be used to irrigate plants because it contains a lot of C-organic nutrients, potassium, ammonia (NH3), nitrate (NO3), nitrite (NO2), pH, nitrogen and phosphorus needed by plants. The advantage of giving catfish waste fertilizer to plants is that the plants become healthier, greener, fresher, more durable and do not turn yellow quickly.